THE CORRELATION OF RELATIONSHIP INTEREST IN LEARNING AND SELF EFFICACY IN ACHIEVEMENT OF STUDENTS IN THE TWO AND FOURTH SEMESTER OF THE 3-D PROGRAMMIDWIFERY STIKES PPNI MOJOKERTO - Puji Suryantini, Naning (JURNAL KEPERAWATAN SEHAT, 2015)
Background :The problems facing the world today is the low educational achievement of student learning . Learning achievement is the main yardstick to determine the success of ones learning . This problem is often associated with learning and confidence in the ability of the ( Self Efficacy ) students . Where every student has a learning interest and confidence in the ability of the ( Self Efficacy ) which varies according to the nature and personality . So this will affect the outcome of learning ( learning achievement ) students .Objectives :( 1 ) Analyze the relationship between Interest in learning the fourth semester student learning achievement in 3-D Program Midwifery Stikes PPNI Mojokerto Healthy Development in 2015 . ( 2 ) Analyze the relationship between Self Efficacy by Achievement fourth semester student in the D - 3 Program Midwifery Stikes PPNI Mojokerto Healthy Development in 2015 .Methods :The research used in this study is a quantitative correlation with cross-sectional approach . The study was conducted on 129 respondents taken by engineering types Proportional Probability Sampling Random Sampling .Instrument :The collection of data about their learning and Self Efficacy students using a Likert scale questionnaire of attitudes . While data of student achievement of learning outcomes seen ( Summative test ) fourth semester .Results :( 1 (1) Simultaneously, interest and Self eficacy significantly related to the achievement of students with grades of F> F is 58.014> 3.07, then Ho is rejected. (2) Partially Self eficacy interests and significantly related to the achievement of students with t-count> t table (2,973> 1,658) for the variables of interest and t count> t table (2,464> 1,658) for the variable self eficacy. (3) Variable Interests and Self eficacy by 47.7% have influence on student achievement while the remaining 52.3% is influenced by other variables besides Interests and Self eficacy are not revealed in this study..Conclusion :here is a relationship variable interest in learning and Self-Efficacy students with achievement of students in the fourth semester Prodi D-3 Midwifery Stikes PPNI Mojokerto Healthy Development in 2015Keywords : Interest in learning , Self- Efficacy , Achievement two and fourth semester students